Farewell to Work - life Balance, Compliments to Work - Life Integration - Dayang Kartini, Abang Ibrahim; Victoria, Jonathan (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Work- life balance is an old maxim; one needs to integrate work into one’s life’. These days, proficient employees in technical and management specialties are consciously deciding to work for companies that give them much more than just an attractive job. Watch out Boss! You need to revive and take action to accommodate the needs of your individual employees. One may not entirely agree with the statement, however this response may change if you hear a great deal of people talking about the concept of integration in their work/life.